(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The study ‘Reconstruction of stature by percutaneous measurement of foot’ is a part of our research project ‘Reconstruction of stature from the parts of upper and lower extremities,’ of which regression equations and multiplication factors are derived for the estimation of height from the distal part of upper extremity (combined length of forearm and hand) and from leg. For stature from foot, standing height and length of right and left feet were measured in 100 adult male and female medical students of 19–25 years and analysed statistically to establish relation between height and length of foot them. Regression equations are derived separately for male and female and these are 3.35X+82.6 and 3.42X+75.8, respectively, where X stands for length of foot. By taking the foot length value of different subjects their stature is calculated and compared with the corresponding real standing height and these were close (±3 cm) in most of the cases. Multiplication factor is also calculated, which is 6.49 for male and 6.65 for female. By using these factors the calculated stature is more than ±5 cm in nearly one-third of the cases, suggesting it less reliable than regression equation.